An experimental investigation on the influence of piston bowl geometry on RCCI performance and emissions in a heavy-duty engine. (October 2015) - Benajes, Jesús; Pastor, José V.; García, Antonio; Monsalve-Serrano, Javier
Highlights: Great influence of piston geometry at low load using single injection strategies. Enhanced combustion development at mid load through optimized piston surface area. Double injection allows ultra-low NOx and soot levels for the three piston geometries. Unacceptable soot emissions at high load using single injection and bathtub geometry. Stepped geometry leads to ultra-clean combustion with lower fuel consumption than CDC. Abstract: This experimental work investigates the effects of piston bowl geometry on RCCI performance and emissions at low, medium and high engine loads. For this purpose three different piston bowl geometries with compression ratio 14.4:1 have been evaluated using single and double injection strategies. The experiments were conducted in a heavy-duty single-cylinder engine adapted for dual fuel operation. All the tests were carried out at 1200 rev/min. Results suggest that piston geometry has great impact on combustion development at low load conditions, more so when single injection strategies are used. It terms of emissions, it was proved that the three geometries enables ultra-low NOx and soot emissions at low and medium load when using double injection strategies. By contrast, unacceptable emissions were measured at high load taking into account EURO VI limitations. Finally, the application of a mathematical function considering certain self-imposed constraints suggested that the more suitable piston geometry for RCCI operation is the stepped one, which has a modified transition from the center to the squish region and reduced piston surface area than the stock geometry.